2015
DOI: 10.1002/chem.201500131
|View full text |Cite
|
Sign up to set email alerts
|

Bridgehead Substitution via Putative Norborn‐1‐en‐3‐ones: Application in the Synthesis of Complex Molecules

Abstract: The base-mediated formation of a bridgehead double bond in a bicyclo[2.2.1]heptane system (anit-Bredt molecules) is described. The synthesis of exocyclic norbornyl enones by Wittig reaction of α-diketones is reported. These enones and their Michael adducts are used as substrates for the generation of transient bridgehead enones and their trapping with MeOH and H2 O. Bridgehead alcohols are easily synthesized from norbornyl enones and are exploited for the diversity oriented synthesis of frameworks of natural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…During the course of our studies on base mediated bridgehead elimination and substitution reactions, 36 we observed the formation of a twist-brendane derivative 5 through intramolecular enolate alkylation in 70% yield along with the originally intended product 6 (yield 17%) from 4 (Scheme 1).…”
Section: Resultsmentioning
confidence: 98%
“…During the course of our studies on base mediated bridgehead elimination and substitution reactions, 36 we observed the formation of a twist-brendane derivative 5 through intramolecular enolate alkylation in 70% yield along with the originally intended product 6 (yield 17%) from 4 (Scheme 1).…”
Section: Resultsmentioning
confidence: 98%